PASO en Buenos Aires: desarrollo del proyecto de primarias, sanción y cambios de la ley provincial (Colección, 2019)
Law No. 14.086 – Open, Mandatory and Simultaneous Primary Elections (EPAOS) was sanctioned in the Buenos Aires state legislature in 2009, following the steps of the national primaries law. This paper analyzes in depth the reasoning behind the bill’s proposal, the debate around it and the changes it underwent before its approval. In addition, we will compare the main differences between the EPAOS and older primary elections laws and contrast the national and subnational legislation. Finally, we will study the impacts of the new regulation on the political system.